2005
DOI: 10.1002/biof.5520230206
|View full text |Cite
|
Sign up to set email alerts
|

Zinc induced apoptosis in HEP-2 cancer cells: The role of oxidative stress and mitochondria

Abstract: Induction of apoptosis by zinc sulfate was investigated during 96 h exposure on the cancer Hep-2 cell line. During 48 h of exposure, zinc translocated into mitochondria and stimulated production of reactive oxygen species (ROS), affected cellular GSH management and induced moderate activation of p53 and dissipation of mitochondrial membrane potential. In Zn-exposed cells, mitochondria released cytochrome c and AIF, whose translocation to the cytoplasm or the nucleus coincided with the activation of apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…However, contrasting data are reported in literature, particularly on the effects of zinc on apoptosis. We assume that such discrepancies may be related, at least in part, to the wide range of zinc concentrations used in different studies (Truong-Tran et al 2000;Nodera et al 2001;Lambert et al 2001;Schrantz et al 2001;Rudolf et al 2005). In this context, we report in the present study that physiological concentration of zinc ions (12.5 lM) affects in vitro both spontaneous and oxidative stress-induced apoptosis.…”
Section: Discussioncontrasting
confidence: 48%
“…However, contrasting data are reported in literature, particularly on the effects of zinc on apoptosis. We assume that such discrepancies may be related, at least in part, to the wide range of zinc concentrations used in different studies (Truong-Tran et al 2000;Nodera et al 2001;Lambert et al 2001;Schrantz et al 2001;Rudolf et al 2005). In this context, we report in the present study that physiological concentration of zinc ions (12.5 lM) affects in vitro both spontaneous and oxidative stress-induced apoptosis.…”
Section: Discussioncontrasting
confidence: 48%
“…Similarly, zinc replenishment in rats rapidly induces apoptosis in esophageal epithelial cells and substantially reduces the development of tumors; and the treatment increases the level of Bax [40]. Rudolf et al [48] reported that zinc acts both directly and indirectly on mitochondria to induce apoptosis in HEP-2 cancer cells. Bae et al [47] also determined the effect of zinc treatment of human epithelial ovarian cancer cells on the maconitase activity.…”
Section: Tumor Suppressor Effects Of Zinc In Other Tumor Cellsmentioning
confidence: 99%
“…The fact that free zinc levels did not dwindle at later treatment periods indicate that the speed and extent of incoming zinc pools was clearly exhaustive for any homeostatic mechanisms the cells might otherwise have employed, thereby establishing a situation which might better reflect real conditions within an organism. From our previous experiments we know that in Hep-2 cells zinc induces apoptosis, which is characterized by the involvement of oxidative stress, p53 and mitochondria, and which is executed both caspase-dependently and -independently (15). Hence we wanted to know more details about the role of p53 in this process and, namely, to explore a mechanism whereby this protein could be activated.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work we discovered that treatment of Hep-2 cells with external zinc during 96 h induces p53-dependent as well as -independent apoptosis (15). To verify the involvement of p53 in cell injury and apoptosis of Hep-2 cells subacutely exposed to external zinc during 24 h, we employed Pifithrin-α, a specific p53 inhibitor, and determined the rate of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation